Analisis Risiko Faktor Keterlambatan Pengiriman Ekspor Di Perusahaan Freight Forwarding Dengan Metode House Of Risk - Oktavianingrum, Tesalonika; Pratiwi, Sekar Widyastuti; Wiguna, Esa Setia (Institut Transportasi dan Logistik Trisakti, 2025)
PT.XYZ is one of the companies engaged in freight forwarding services. In this study, we analyzed the risk factor of delays in export shipments where there was data on delays in January-March 2023, causing export shipments to not run properly and causing losses to the company. The purpose of this research is to identify the causes of risks that occur and minimize the causes of these risks. The method used in the research is supply chain activity mapping using Supply Chain Operation Reference and House of Risk. The results of this study were 12 risk events and 11 risk agents. By using a pareto diagram to determine the priority of risk agents based on the highest value, five dominant risk agents were obtained, namely A2 (Human error), A11 (Late loading of goods), A10 (Trucks operate side by side with employee return hours), A8 (Not finished production) and A6 (Container runs out). Based on these dominant risk agents, 9 mitigation actions can be implemented. Of the 9 mitigation strategies by considering the effectiveness in its application, 5 main strategies were obtained, namely providing training (PA1), establishing communication with related parties (PA4), providing rewards or punishments to employees (PA2), making fleet travel schedules (PA5) and making education to shippers (PA3).